Fenologia e sazonalidade da condição corpórea de morcegos fitófagos no Pantanal - VINÍCIUS SANTOS PEREIRA (2025)
The Pantanal, a vast sedimentary plain in South America, is home to 66 species of bats, which are important for pollination and seed dispersal. The behavior and reproduction of these mammals are influenced by climatic seasonality, which reflects variations in resource availability. This study aims to describe the reproductive phenology and monthly variation in body condition of frugivorous and nectarivorous bats, and to evaluate the relationship of these variables with temperature, rainfall, and fruit and flower richness. A database with 4,867 captures in the subregions of Nhecolândia, Miranda, and Aquidauana over 10 years was used, with records of phenophases and measurements of body condition. The results indicated significant variations in the body condition index (BCI) according to the climatic seasons and resource availability. Pregnant and adult females presented higher BCI in the wet season, with greater availability of fruits and flowers, while the lowest values ​​occurred in the dry season. Among the species, Artibeus lituratus and Carollia perspicillata showed peaks of ICC in the wet season, while Sturnira lilium showed a negative correlation between fruit richness and ICC. Among the nectarivores, Anoura caudifer had a positive relationship between flower richness and ICC, and Glossophaga soricina with rainfall. Omnivorous species such as Phyllostomus discolor and Phyllostomus hastatus did not show significant effects of environmental variables. These results demonstrate that the variation in ICC is strongly associated with seasonality and availability of food resources.